2020
DOI: 10.1038/s41598-020-61735-3
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium mishandling in absence of primary mitochondrial dysfunction drives cellular pathology in Wolfram Syndrome

Abstract: Wolfram syndrome (WS) is a recessive multisystem disorder defined by the association of diabetes mellitus and optic atrophy, reminiscent of mitochondrial diseases. The role played by mitochondria remains elusive, with contradictory results on the occurrence of mitochondrial dysfunction. We evaluated 13 recessive WS patients by deep clinical phenotyping, including optical coherence tomography (OCT), serum lactic acid at rest and after standardized exercise, brain Magnetic Resonance Imaging, and brain and muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 64 publications
(73 reference statements)
2
40
0
Order By: Relevance
“…In line with the Wfs1 calcium modulation feature, our previously published data have shown that cytosolic calcium signal in response to glutamate or KCl stimulation was twice lower in Wfs1 deficient neurons (Cagalinec et al 2016). Analogical decrease of the cytosolic calcium release amplitude has been observed recently in WS patients' derived fibroblasts after stimulation with bradykinin (La Morgia et al 2020) or histamine (Angebault et al 2018). Moreover, Zatyka et al (2015) have demonstrated that the Wfs1 co-immunoprecipitates with sarcoplasmic-endoplasmic reticulum calcium ATPase (SERCA) and that it negatively regulates SERCA expression.…”
supporting
confidence: 82%
“…In line with the Wfs1 calcium modulation feature, our previously published data have shown that cytosolic calcium signal in response to glutamate or KCl stimulation was twice lower in Wfs1 deficient neurons (Cagalinec et al 2016). Analogical decrease of the cytosolic calcium release amplitude has been observed recently in WS patients' derived fibroblasts after stimulation with bradykinin (La Morgia et al 2020) or histamine (Angebault et al 2018). Moreover, Zatyka et al (2015) have demonstrated that the Wfs1 co-immunoprecipitates with sarcoplasmic-endoplasmic reticulum calcium ATPase (SERCA) and that it negatively regulates SERCA expression.…”
supporting
confidence: 82%
“…However, a case of homozygous CISD2 mutation associated with “classical” WS1 has been reported [ 253 ]. Interestingly, a proteomic study evidenced the presence of Wfs1 in the MAMs fraction isolated from mouse brain tissues [ 237 ], and we recently confirmed that WFS1 is enriched in the MAMs also in human cell lines [ 19 ]. These findings suggest that Wolfram syndrome, and associated optic atrophy, may be due to alterations in MAMs-related processes, as in CMT2A.…”
Section: Mitochondria-associated Membranes: the Case Of Wolfram Syndrome And Morementioning
confidence: 88%
“…These findings suggest that Wolfram syndrome, and associated optic atrophy, may be due to alterations in MAMs-related processes, as in CMT2A. According to this consideration, WS1 fibroblasts show reduced mitochondrial Ca 2+ uptake driven by altered Ca 2+ release from ER and altered ER-mitochondria contacts, whereas mitochondrial dynamics and morphology are not affected [ 18 , 19 ]. The increase in non-oxidative glycolysis, documented by high lactate levels in plasma of WS1 patients, in absence of defective mitochondrial respiration, and enhanced extracellular acidification rate (ECAR) in fibroblasts, may be related to a reduced activity of PDH, as regulated by mitochondrial Ca 2+ , and to diabetes [ 19 ].…”
Section: Mitochondria-associated Membranes: the Case Of Wolfram Syndrome And Morementioning
confidence: 99%
See 2 more Smart Citations